Differences in Knowledge, Attitude, and Behavior towards HIV/AIDS and Sexually Transmitted Infections between Sexually Active Foreign and Chinese Medical Students. (19th April 2016) - Kuete, Martin; Huang, Qiao; Rashid, Abid; Ma, Xiu Lan; Yuan, HongFang; Escalera Antezana, Juan Pablo; Yeltay, Rakhmanov; Rao, Meng; He, Qian; Xiong, ChengLiang; Zhang, HuiPing
Abstract : Although the prevalence of human immunodeficiency virus (HIV) decreased in the last decade worldwide, the number of deaths due to HIV/AIDS and communicable diseases including syphilis, hepatitis, and tuberculosis had dramatically increased in developing countries. Education and behavior are incredibly important factors to prevent these diseases' spread. This study highlights the range of differences in knowledge, attitude, and behavior of 434 sexually active medical students towards HIV/AIDS and sexually transmitted infections (STIs). Because the surveyed population constitutes the forefront of healthcare providers and was originated from different area of the world, this is the first time a study sought to investigate the behavioral attitude of this group of population irrespective of the three levels of their academic and professional knowledge. Several factors including sociodemographic characteristics, sexual behavior, HIV/AIDS, and STIs related patterns play a key role in medical student attitude and behavior towards people infected with HIV/AIDS and STIs. Our findings add consistent value in prior studies which aimed to stop new infections and also imply further investigations on the management of the studied infections by medical students. The present study arouses much interest among participants and provides evidence of reinforcing medical students' education on HIV/AIDS and STIs.